Effectiveness of Organic Fertilizer Enriched with Humic Acid on Soil Chemical Quality, Nutrient Uptake, and Shallot Yield in Calcareous Soils - Rupa Matheus; Donatus Kantur (The University of Lampung, 2025)
Calcareous soils have great potential for the development of food crops and horticulture, but they are constrained by high pH, low organic matter content, and less than optimal cation exchange capacity, thus affecting the availability of nutrients. This study aims to evaluate the effectiveness of organic fertilizer enriched with humic acid on soil chemical quality, nutrient uptake, and yield of shallots on calcareous soils. The study was designed with two factors, namely type of organic fertilizer (manure and bokashi) and concentration of humic acid (0%, 10%, and 20%) added to the organic fertilizer. The results of the study showed that the application of organic fertilizers, both manure and bokasih, had a similar effect on soil quality and shallot yields. However, the addition of humic acid at a concentration of 20% significantly improved the chemical properties of the soil, nutrient uptake (especially nitrogen and potassium), as well as the yield component of shallots when compared to the concentration of 10% and control. The addition of humic acid has been proven to be effective in improving nutrient availability and supporting plant growth. This innovation can be an effective solution to improve the quality of calcareous soils and agricultural products, especially shallots, which supports sustainable and environmentally friendly agriculture. Keywords: Calcareous soil, Humic acid, Nutrient uptake, Organic fertilizer, Shallots.